KONSEP TUHATN SUKU DAYAK BARAI KAYAN-HILIR KALIMANTAN BARAT DALAM TERANG FILSAFAT DIALOG MARTIN BUBER - Siong Siong; Armada Ryianto; Mathias Adon (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
This research is motivated by the ambiguous understanding of the Dayak Barai in interpreting God as the highest form; God for the Dayak Barai as something far away so the name God is often absent in their rituals. The purpose of this study is to introduce a philosophical, critical and directed relationship to the giver of life, namely God of the Dayak Barai himself. Another purpose of this paper is to explore the philosophical value of the local wisdom of the tribes in Indonesia, namely the Dayak Barai tribe. This theme has never been raised in any journal. The locus of this research is the culture of the Dayak Barai tribe, Kayan Hilir District. The methodology used in this study is a comparative study with a descriptive narrative approach. I came to the discovery that the Dayak Barai people from the beginning believed that there was only one God. The relevance of Martin Buber's dialogue philosophy for the Barai Dayak people is that they are brought to a new foundation that the building of their relationship with God originates and ends from the one God. This research ultimately opens new horizons for religious life in Indonesia that the highest reality worshiped in every religion and belief is essentially the same God, but is lived in a different way.